Saving Behavior and the Asset Price "Bubble" in Japan : Analytical Studies - Meredith, Guy (Occasional Papers; Occasional Paper, 1995)
This volume brings together various analytical studies the IMF staff has undertaken on the Japanese economy, focusing on two areas of particular interest for both longer-term economic performance and recent cyclical developments. The first is Japan's saving behavior, the second is the remarkable swing in asset prices that occurred in the late 1980s and early 1990s.